Penerapan Algoritma A-Star Dalam Mencari Jalur Tercepat dan Pergerakan NonPlayer Character Pada Game Petualangan Labirin Tech-Edu - Bagus Tegar Dwi Irianto; Septi Andryana; Aris Gunaryati (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2021)
Games are a means of entertainment that are in electronic media such as smartphones that are made as attractive as possible so that players get inner satisfaction. The development of the game industry is growing quite fast from mobile to desktop. There are many categories of games such as action, strategy, sports, shooter, adventure and simulation. Adventure games are one category of games where players are trained to think in order to complete the game. There are many things that need to be considered, such as visuals on maps or interactions with NPCs (NonPlayer Character), by utilizing technology now learning can be delivered through a game. The characteristics of entertaining games and interesting visual activities will make learning more attractive. Making games will of course use algorithms as features or systems in game making. The a-star algorithm is one that is widely used in making maze games. The a-star algorithm can be applied to the help of the fastest path or movement of the NPC. The purpose of the research is to make a maze educational game using the a-star algorithm as the fastest path search and NPC movement. The test results on games on seven devices got the results that they were successfully run, in CPU usage on mobile devices a minimum of 7% and a maximum of 57%. CPU usage on desktop devices is a minimum of 2% and a maximum of 33%.